1992
DOI: 10.1007/bf02171758
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of RBS (rice bran saccharide) on ENNG-induced carcinogenesis

Abstract: We examined whether orally administered RBS (rice bran saccharide), prepared from rice bran by hot water extraction, increases immunocompetence, inhibits gastrointestinal carcinogenesis with N-ethyl-N'-nitro-N-nitrosoguanidine (ENNG) or shows an antitumor effect. After the administration of RBS, phytohemagglutinin (PHA)- and pokeweed mitogen (PWM)-stimulated blastogenesis of lymphocytes derived from the mesenteric lymph nodes and peripheral blood was enhanced, and the helper/suppressor T-cell ratio was elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The control mechanisms of the immune system responsible for anticancer activity, combating infections, complement activation, macrophage activation, etc., are responsive to active components of polysaccharides. Reports showing that hemicellulose present in the cell wall of rice bran enhances anticancer immune function 6,7 have prompted active research into the development of rice branderived polysaccharides as new BRMs. However, in most cases, the immune-enhancing polysaccharides contained in rice bran are present as part of a complex with dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The control mechanisms of the immune system responsible for anticancer activity, combating infections, complement activation, macrophage activation, etc., are responsive to active components of polysaccharides. Reports showing that hemicellulose present in the cell wall of rice bran enhances anticancer immune function 6,7 have prompted active research into the development of rice branderived polysaccharides as new BRMs. However, in most cases, the immune-enhancing polysaccharides contained in rice bran are present as part of a complex with dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the abundance of some functional compounds, rice bran has drawn the attention of chemists and pharmacologists recently (Azizah and Yu, 2000;Gurpreet and Sogi, 2007;Juan et al, 2006). Among the functional compounds, many biological active polysaccharides extracted from rice bran appeared to elicit excellent physiological properties in maintaining health and preventing diseases such as anti-tumor (Takeshita et al, 1992), enhancing the immune function (Tzianabos, 2000) and increasing the peripheral blood lymphocytes (Takenaka and Itoyama, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Rice bran saccharide (RBS), a polysaccharide component contained in rice bran, exhibits anti-tumor capabilities [ 4 ]. In a study on tumor prevention and suppression of tumor growth in rats, RBS was found to suppress carcinogenesis and to prolong survival rate [ 9 ]. We have not seen any published literature regarding the fractionation of the bran layer to examine RBS concentration.…”
Section: Introductionmentioning
confidence: 99%
“…We have not seen any published literature regarding the fractionation of the bran layer to examine RBS concentration. If RBS can be extracted successfully, rice bran could be a source for a high-value pharmaceutical product [ 9 ].…”
Section: Introductionmentioning
confidence: 99%